Решение уравнений магнитного поля в прямоугольном пазу с током, имеющем зону с постоянной магнитной проницаемостью - Загирняк, М.В.; Бранспиз, Ю.А.; Вельченко, А.А. (Технічна електродинаміка, 2012)
The task of determination of distribution of vector magnetic potential is examined in a rectangular area (limited to the environment with endless constant magnetic permeability) with a current zone and zone of material with permanent constant magnetic permeability. For these two zones it is decided the method of division of variables accordingly equations of Poisson and Laplace with the concordance of border terms on the contiguous border of zones. Analytical expressions are got for vector potentials of these zones as rows with the trigonometric and exponential functions of coordinates with the set coefficients allowing to determine distribution of magnetic flux in the examined rectangular area.